Lumbo-sacral motion conserved after isthmic reconstruction: Long-term results. (February 2014) - de Bodman, C.; Bergerault, F.; de Courtivron, B.; Bonnard, C.
Purpose: The purpose of this study was to analyze the clinical and radiological results of repair of the interarticularis pars defect by a modified Buck's repair technique in patients with symptomatic spondylolysis with grade 1 spondylolisthesis. Summary of background data: These patients with painful spondylolisthesis are the most eligible for direct repair of the defect rather than lumbo-sacral fusion in an attempt to save motion segments. Methods: Forty-six patients with symptomatic spondylolysis with grade 1 spondylolisthesis and normal L4–L5 and L5–S1 disks, following the failure of conservative treatment, underwent surgery between 1988 and 2010. All interventions involved direct pars repair by a modified Buck's repair technique with internal fixation of the defect using screws and cancellous bone grafting. The Oswestry Disability Index (ODI) was used to evaluate the functional outcome. Healing of the pars defect was assessed by plain radiographs and computed tomography (CT) scanning. Motion of the L4–L5 and L5–S1 segments was measured with dynamic radiographs in flexion and extension. Results: Thirty-five patients were evaluated. The mean follow-up period was 10 years. Functional outcome was excellent in 22 patients (ODI ≤ 10) and good for 8 patients (10 < ODI ≤ 20); five patients continued to have pain (ODI >20). Isthmus bone union occurred in 32 of 35 patients (91.4 %). L4–L5 motion was conserved with a mean angle of 11.8° (0–22); the mean lumbo-sacral angle was 9.9° (0–21). Conclusion: Direct repair of spondylolisthesis was described to avoid fusion in young patients with slight slipping and painful symptoms. A modified Buck's repair technique allows the conservation of L4–L5 motion with a rate of consolidation comparable to other series. The anatomy and stability of the spine were normalized by restoring the continuity of the loose posterior elements using this modified Buck's technique.